Perspectives on the synthesis and use of ageladine A. Issue 29 (15th July 2015) - Mordhorst, Thorsten; Bickmeyer, Ulf
Graphical abstract: Highlights: A modified synthesis to reveal gram-scales of ageladine A is demonstrated. An increased Stokes shift of ageladine A in living transparent animals is demonstrated. The Stokes shift in flatworms matches DAPI filter settings. Abstract: Focusing on the marine-derived alkaloid ageladine A ([4-(4, 5-dibromo-1 H -pyrrol-2-yl)]-1 H -imidazo[4, 5- c ]pyridin-2-amine trifluoroacetate), we combined and modified published strategies to develop a synthesis method with easily managed reaction steps that allows gram-scale batch synthesis. On exploration additional features of the fluorescent properties of the compound were revealed. In tissues and cells of a marine flatworm, the emission profile shifted to longer wavelengths than in water. The fluorescence emission maximum shifted around 30–450 nm and the profile showed sufficient intensity at approximately 550 nm and above.